SN 2015as: a low-luminosity Type IIb supernova without an early light-curve peak. Issue 3 (22nd February 2018) - Gangopadhyay, Anjasha; Misra, Kuntal; Pastorello, A; Sahu, D K; Tomasella, L; Tartaglia, L; Singh, Mridweeka; Dastidar, Raya; Srivastav, S; Ochner, P; Brown, Peter J; Anupama, G C; et al.
Abstract: We present results of the photometric (from 3 to 509 d post-explosion) and spectroscopic (up to 230 d post-explosion) monitoring campaign of the He-rich Type IIb supernova (SN) 2015as. The ( B − V ) colour evolution of SN 2015as closely resemble those of SN 2008ax, suggesting that SN 2015as belongs to the SN IIb subgroup that does not show the early, short-duration photometric peak. The light curve of SN 2015as reaches the B -band maximum about 22 d after the explosion, at an absolute magnitude of −16.82 ± 0.18 mag. At ∼75 d after the explosion, its spectrum transitions from that of a SN II to a SN Ib. P Cygni features due to He i lines appear at around 30 d after explosion, indicating that the progenitor of SN 2015as was partially stripped. For SN 2015as, we estimate a 56 Ni mass of ∼0.08 M⊙ and ejecta mass of 1.1–2.2 M⊙, which are similar to the values inferred for SN 2008ax. The quasi-bolometric analytical light-curve modelling suggests that the progenitor of SN 2015as has a modest mass (∼0.1 M⊙ ), a nearly compact (∼0.05 × 10 13 cm) H envelope on top of a dense, compact (∼2 × 10 11 cm) and a more massive (∼1.2 M⊙ ) He core. The analysis of the nebular phase spectra indicates that ∼0.44 M⊙ of O is ejected in the explosion. The intensity ratio of the [Ca ii ]/[O i ] nebular lines favours either a main-sequence progenitor mass of ∼15 M⊙ or a Wolf–Rayet star of 20 M⊙ .